2013
DOI: 10.1016/j.neurobiolaging.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β peptides modify the expression of antioxidant repair enzymes and a potassium channel in the septohippocampal system

Abstract: Alzheimer's disease (AD) is a progressive, neurodegenerative brain disorder characterized by extracellular accumulations of amyloid β (Aβ) peptides, intracellular accumulation of abnormal proteins, and early loss of basal forebrain neurons. Recent studies have indicated that the conformation of Aβ is crucial for neuronal toxicity, with intermediate misfolded forms such as oligomers being more toxic than the final fibrillar forms. Our previous work shows that Aβ blocks the potassium (K+) currents IM and IA in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Furthermore, changes in function and neuronal damage might involve multiple pathways that lead the oxidative stress. Besides that, studies also showed that changes in the potassium levels in the brain's interstitial fluid influence the generation of action potentials in neurons and thus directly affect neuronal and synaptic functions . So, the findings for potassium levels agree with studies that show that the potassium levels are changed in the brains with AD.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, changes in function and neuronal damage might involve multiple pathways that lead the oxidative stress. Besides that, studies also showed that changes in the potassium levels in the brain's interstitial fluid influence the generation of action potentials in neurons and thus directly affect neuronal and synaptic functions . So, the findings for potassium levels agree with studies that show that the potassium levels are changed in the brains with AD.…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, for male groups, a decrease in the potassium levels in the temporal cortex, hippocampus, cerebellum, and substantia nigra was observed. Durán‐Gonzáles et al showed that Aβ can lead to a reduced expression of a particular ion channel gene and demonstrated that K + channel genes are susceptible to oligomeric Aβ influence in rats. Furthermore, changes in function and neuronal damage might involve multiple pathways that lead the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular accumulation resulted in tubulin beading and endosomal leakage [127]. In vivo injections into the CA1 region of the hippocampus resulted in time-dependent effects on the expression levels of multiple genes distant from the injection site [34]. With respect to the prion-like potential of cell-to-cell transfer, it has been found that an unusual oligomeric species, large fatty acid-derived AβOs that are 12–18mers and form “off pathway”, can recruit Aβ42 at expense of fibril formation and self-replicate [89].…”
Section: Are Aβos Extracellular Intracellular or Both?mentioning
confidence: 99%
“…These results show that limited Aβ-induced hippocampal lesions lead to an overall damage of vulnerable septal neuronal populations, as supposed by the authors, most likely by Aβ interaction with septo-hippocampal axon terminals. It has been shown that in the medial septum the expression of several genes related to oxidative stress was lower 24 h after injection of fibrillar Aβ(1-40) into the hippocampus, including superoxide dismutase-1 (SOD1), 8-oxoguanine DNA glycosylase, and monoamine oxidase A; however, expression of SOD1 was significantly increased 1 month after the treatment [50]. In the lateral septum, which does not contain cholinergic neurons, and in the hippocampus all these genes were overexpressed.…”
mentioning
confidence: 99%